Planificación tributaria de la compañía de taxis Wilson Morocho s.a. de la ciudad de Riobamba, provincia de Chimborazo, en el año 2016, para disminuir el riesgo tributario. - Pusay Chiriboga, Hilda Rebeca (2017)
The research titled “TAX PLANNING AT TAXI COMPANY WILSON MOROCHO A.S. IN RIOBAMBA CITY, CHIMBORAZO PROVINCE, IN THE YEAR 2016, TO REDUCE THE TAX RISK” was developed with the aim to identify if in the enterprise plans the tax management. Referential Framework the Problem statement, problem formulation the objectives of the research and the justification why the research was done, were established. The theoretical framework it describes the Enterprise general characteristics, research variables definitions, and basic aspects: Tax Planning and Tax Risk. Methodological Framework, it is about the research method employed, its type and design, population and study sample, and the techniques and instruments to collect the data. As well as the techniques to analyze the results. At the results and discussion, it presents the information gathered through the observation of the activities of the Enterprise; the survey applied to people involved in tax planning, and the survey carried out to the suppliers. It presents the conclusions and recommendations that had been reached at the end this research project.